Gaya Konsumtif Gen Z Melalui Akun Tiktok Shop dalam Pembelian Produk Fashion Baju pada Kelas KPI 5D - Rio Erdi Pamungkas; Fantri Elistia Ainu; Pia Khoirotun Nisa; Muhammad Akbar Chaniago; Muhammad Salman Husairi; Azizah Salma Adinda (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This research examines the consumptive style of Gen Z through TikTok Shop in purchasing fashion products, especially clothes. The background of the research focuses on the dominance of social media that influences the consumption patterns of the younger generation. The research uses a phenomenological approach to understand students' experiences in shopping at TikTok Shop. Data collection techniques include observation and in-depth interviews. The results show that TikTok Shop utilizes personalization algorithms, creative video content, and massive promotions to attract the attention of Gen Z. Purchasing decisions are often influenced by trends, influencer recommendations, and discounts that create a FOMO (Fear of Missing Out) effect. While offering convenience and an interactive shopping experience, this impulsive consumption pattern poses the risk of product quality disappointment and unplanned spending. The implications of this research highlight the need for consumer education to raise awareness about wise shopping. In addition, industry players are expected to design ethical and sustainable marketing strategies to support more rational consumption behavior.